Pengaruh Ekstrak Kulit Manggis Terhadap Histologi Jumlah Sel Nekrosis Pulau Langerhans Tikus Putih Jantan Hiperglikemik - Lewi Santoso, Anna; Lewi Santoso, Jemima (Universitas Ciputra Surabaya, 2025)
The aim of this study was to analyze the histological profile of necrotic cell counts in the islets of Langerhans in hyperglycemic male white rats given mangosteen peel extract. Hyperglycemic conditions can form reactive oxygen species (ROS)/free radicals. Excessive ROS can cause oxidative stress and exacerbate cell necrosis in the islets of Langerhans. Mangosteen peel contains the antioxidant compound, Xanthone, an organic compound derived from diphenyl-γ-pyrone that can neutralize ROS and inhibit islet cell necrosis. This study employed a randomized post-test-only control group design. Four groups of male white rats: the untreated group (normal), the alloxan-induced group, the 250, and 500 mg/kgBW dose groups. The data results were tested using Kruskal-Wallis. The results of the study indicated that mangosteen peel extract had an effect on the histological profile of necrotic cell counts in the islets of Langerhans in male white rats experiencing hyperglycemia; with the number of necrotic cells decreased, the mangosteen peel extract dose of 250 mg was 19.2, and the dose of 500 mg was 18.4. Mangosteen peel extract had an effect on necrotic cells in the islets of Langerhans